Effectiveness Of The “Nganak Kodek” Android App In Enhancing Knowledge Of Birth Preparedness, Breastfeeding Technique, And Exclusive Breastfeeding Among Adolescent Primigravidas - Hamidiyanti, Baiq Yuni Fitri; Pratiwi, Intan Gumilang; Sulianty, Ati; Demir, Emine (Jurnal Kesehatan Manarang, 2025)
Stunting remains a major public health issue that begins early in life and is stronglyassociated with inadequate maternal care, nutrition, and infant feeding practices.Pregnant adolescents are particularly vulnerable due to limited knowledge andreadiness for childbirth and breastfeeding, which are crucial for preventing stuntedgrowth in infants. This quasi-experimental study aimed to evaluate the effectivenessof a Mobile WebApp–based intervention in increasing knowledge related to childbirthreadiness and breastfeeding as part of stunting prevention among pregnant adolescentsin Narmada Subdistrict, West Lombok Regency, Indonesia. A total of 60 pregnantadolescents who met the inclusion criteria (aged 15–19 years, first pregnancy, andable to use smartphones) were selected using purposive sampling. The instrument, a25-item questionnaire, was developed based on the Health Belief Model (HBM),covering aspects of perceived susceptibility, perceived benefits, and cues to actionrelated to maternal and infant health. The instrument underwent expert validity testingby three midwifery and maternal health specialists and achieved a validity coefficientof r = 0.78 and a Cronbach’s alpha reliability value of 0.86, indicating goodconsistency. The one-month Mobile WebApp intervention provided educationalmodules on breast care, signs of labor, early initiation of breastfeeding (EIBF),breastfeeding techniques, and exclusive breastfeeding up to six months of age. Datawere analyzed using the Wilcoxon signed-rank test. The results showed a significantimprovement in maternal knowledge after the intervention (p < 0.05). These findingsdemonstrate that the Mobile WebApp effectively enhances pregnant adolescents’readiness for childbirth and breastfeeding, thereby supporting efforts to preventstunting. Integrating mobile health applications into maternal education can strengthenadolescent mothers’ capacity to promote optimal maternal and child health outcomes.